A de novo DDX3X Variant Is Associated With Syndromic Intellectual Disability: Case Report and Literature Review - Chen, Yun; Liu, Kai-Yu; Yang, Zai-Lan; Li, Xiao-Huan; Xu, Rui; Zhou, Hao (Frontiers in Pediatrics, 2020)
De novo DDX3X variants account for 1-3% of intellectual disability (ID) in females and have been occasionally reported in males. Here, we report a female patient with severe ID and various other features, including epilepsy, movement disorders, behavior problems, sleep disturbance, precocious puberty, dysmorphic features and hippocampus atrophy. With the use of family-based exome sequencing, we identified a de novo pathogenic variant (c.1745dupG/p.S583*) in the DDX3X gene. However, our patient did not present hypotonia, which is considered a frequent clinical manifestation associated with DDX3X variants. While hand stereotypies and sleep disturbance have been occasionally associated with the DDX3X spectrum, hippocampus atrophy has not been reported in patients with DDX3X-related ID. The investigation further expands the phenotype spectrum for DDX3X variants with syndromic intellectual disability, which might help to improve the understanding of DDX3X-related intellectual disability or developmental delay.